2004
DOI: 10.1002/jbm.b.30130
|View full text |Cite
|
Sign up to set email alerts
|

Water content and apparent stiffness of non‐caries versus caries‐affected human dentin

Abstract: Caries-affected dentin contains less mineral and more water than surrounding normal dentin. Such dentin should be less stiff and should shrink more than normal dentin when dried. The purpose of this study was to test the relationships between the stiffness, shrinkage, and water content of caries-affected versus normal dentin. Extracted human carious third molars were stained with caries-detector dye and the occlusal surfaces ground down until only caries-affected dentin remained, surrounded by normal dentin. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 23 publications
1
58
0
16
Order By: Relevance
“…These findings corroborate with other studies that evaluated the BS of natural or artificially prepared CAD [28,29]. The higher water volume in CAD [30] reduced calcium, phosphate, and magnesium levels [31] due to successive demineralization cycles, hindering the development of chemical bonds [30] to this tissue. Moreover, the higher porosity of the intertubular dentin and the lower hardness of the tissue [32] could also decrease BS.…”
Section: Discussionsupporting
confidence: 89%
“…These findings corroborate with other studies that evaluated the BS of natural or artificially prepared CAD [28,29]. The higher water volume in CAD [30] reduced calcium, phosphate, and magnesium levels [31] due to successive demineralization cycles, hindering the development of chemical bonds [30] to this tissue. Moreover, the higher porosity of the intertubular dentin and the lower hardness of the tissue [32] could also decrease BS.…”
Section: Discussionsupporting
confidence: 89%
“…Attempts to remineralize demineralized dentin should thus provide for crystallization in the gap zones [Balooch et al, 2008;Bertassoni et al, 2011]. Even though direct comparison cannot be done, it is interesting to note that caries-affected (sclerotic) dentin has similar relative reduction in stiffness (79%) and increase in shrinkage after drying (76%) compared to normal dentin [Ito et al, 2005].…”
Section: Fate Of Dentin Collagen During Caries Demineralization -Rolementioning
confidence: 99%
“…However, experimental studies with rapid de-remineralization cycles do not allow potential time-related changes in the dentin organic matrix that might occur in natural lesions. As pointed out by Ito et al [2005], dentinal carious lesions develop over months and even years, after thousands of episodes of demineralization, neutralization and remineralization. Quantitative characterizations have shown that carious lesions are far from identi- Ito et al, 2005].…”
Section: Fate Of Dentin Collagen During Caries Demineralization -Rolementioning
confidence: 99%
See 1 more Smart Citation
“…In this way a minor amount of energy is required for the ablation of dentin that is more rich in water [ 21 -23 ] and even less for caries [ 24 ], while a greater amount is required for the ablation of decayed or highly mineralised enamel.…”
Section: Fig 77mentioning
confidence: 99%